Pengaruh Ukuran Perusahaan pada Perusahaan Manufaktur Sektor Property, Real Estate dan Building Construction yang terdaftar di Bursa Efek Indonesia Tahun 2017-2020 - Anggun Yuliana, Khrisna; Sulivyo, Lod; Maya Dewi, Faye (JOURNAL INTELEKTUAL, 2022)
Introduction/Main Objectives: To investigate the impact of company size, tax planning, and leverage on earnings management in property, real estate, and building construction companies listed on the IDX from 2017 to 2020. Background Problems: Violating Financial Accounting Standard 44 concerning Accounting for Real Estate Activities (PSAK 44) applies to companies engaged in real estate, even though real estate is not the company's main business. Novelty: Used to obtain secondary data for this research, which uses quantitative methods and financial reporting. Research Methods: Purposive sampling method with a total of 63 property, real estate, and building construction companies for 2017 to 2020, a sample of 21 companies with SPSS 25.  Finding/Results: That company size and tax planning have a negative and significant effect on earnings management and Leverage has no effect on earnings management and the results (f-test) simultaneously have an effect on earnings management. Conclusion: Firm size has a negative impact, tax planning has a negative impact, financial leverage has no earnings management, and claims company size, tax planning, and financial leverage have an impact.